Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Volatile profile analysis and quality prediction of Longjing tea (Camellia sinensis) by HS-SPME/GC-MS - Jie Lin; Yi Dai; Ya-nan Guo; Hai-rong Xu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

Use of reverse genetics to develop a novel marker porcine reproductive and respiratory syndrome virus - Tao Lin; Xiangrui Li; Huochun Yao; Zuzhang Wei; Feifei Tan; Runxia Liu; Lichang Sun; Rong Zhang; Wenliang Li; Jiaqi Lu; Guangzhi Tong; Shishan Yuan (Virus Genes, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Changes in labile soil organic matter fractions following land use change from monocropping to poplar-based agroforestry systems in a semiarid region of Northeast China - Rong Mao; De-Hui Zeng; Lu-Jun Li; Ya-Lin Hu (Environmental Monitoring and Assessment, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Identification and molecular cytology analysis of cold tolerance introgression lines derived from Oryza sativa L. mating with O. rufipogon Griff. - Xiang-Dong Luo; Liang-Fang Dai; Juan-Fang Cao; Shui-Rong Jian; Ya-Ling Chen; Biao-Lin Hu; Jian-Kun Xie (Euphytica, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

A new phenylalkanoid from the rhizomes of Zingiber officinale - Soong-Yu Kuo; Rong-Jyh Lin; Yu-Ting Yeh; Jun-Yen Lee; Chung-Yi Chen (Natural Product Research, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

Relationships between photosystem II efficiency and photochemical reflectance index under different levels of illumination: comparison among species grown at high- and low elevations through different seasons - Jen-Hsien Weng; Shau-Lian Wong; Kuan-Ming Lai; Rong-Jhih Lin (Trees, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

[11C]DAC-PET for Noninvasively Monitoring Neuroinflammation and Immunosuppressive Therapy Efficacy in Rat Experimental Autoimmune Encephalomyelitis Model - Lin Xie; Tomoteru Yamasaki; Naotsugu Ichimaru; Joji Yui; Kazunori Kawamura; Katsushi Kumata; Akiko Hatori; Norio Nonomura; Ming-Rong Zhang; Xiao-Kang Li; Shiro Takahara (Journal of Neuroimmune Pharmacology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)